My Book of Bugs : A Fact-Filled Guide to the Insect World - Hubbard, Ben, 1973- (New York, NY : DK Publishing, 2025)
An "introduction to the seven major insect groups, [including] profiles for over 40 amazing insects, such as the stag beetle, monarch butterfly, and honey bee. Grab your magnifying glass and head out to discover all about insects--their different types, body structures, and behaviors"--
Includes index.
Keywords: Insects -- Juvenile literature; Insects; Arthropods